Inositol Polyphosphate 4-Phosphatase Type II Is a Tumor Suppressor in Multiple Myeloma - Wang, Yafei; Chen, Lin; Li, Qian; Gao, Shuang; Liu, Su; Ma, Jing; Xie, Ying; Wang, Jingya; Cao, Zeng; Liu, Zhiqiang (Frontiers in Oncology, 2022)
Inositol polyphosphate-4-phosphatase type II (INPP4B) has been identified as a tumor suppressor, while little is known about its expression and function in multiple myeloma (MM). In this study, we evaluated the expression of INPP4B in 28 cases of newly diagnosed MM patients and 42 cases of extramedullary plasmacytoma (EMP) patients compared with normal plasma cells, and found that low INPP4B expression was correlated with poor outcomes in MM patients. Moreover, expression of INPP4B in 7 MM cell lines was all lower than that in normal plasma cells. In addition, loss of function of INPP4B promoted cell proliferation in MM cells, however gain of function suppressed MM cells proliferation, and arrested the cell cycle at G0/G1 phage. Meanwhile, knockdown of INPP4B enhanced resistance, but overexpression promoted sensitivity to bortezomib treatment in MM cells. Mechanistically, we found that INPP4B exerted its role via inhibiting the phosphorylation of AKT at lysine 473 but not threonine 308, which attenuated the activation of the PI3K/AKT/mTOR signaling pathway. Therefore, we identified an inhibitory effect of INPP4B in MM, and our findings suggested that loss of INPP4B expression is a risk factor of aggressive MM.